Anthropology and Representations of Magic in Arab Theatrical Text Harut and Marut's Play as a Model: وصال خلفة كاظم البكري (Al-Academy, 2021)
The research (Anthropology and Representations of magic in Arab Theatrical Text, Harut and Marut's play as a Model) is concerned with studying magic and the forms of its presence in the theatrical text in different human cultures where it belongs. The research consists of four chapters. The first chapter includes the research problem that revolves around the following questions: (what is the mechanism of employing magic anthropology and its representations in the Arab theatrical text Harut and Marut's play as a model?), and the research importance which is attributed to the necessity of studying (magic) in the Arab theatrical text as it is considered the inauguration of one of the social phenomena that many researchers in the field of theatre had not been able to delve into it before. The need for this research stems from that fact that it will benefit the researchers and scholar in the colleges and institutes of fine arts and those working in the field of Theatrical literature, as well as determining the objective which focused on defining the subject of (Anthropology and Representations of Magic in Arab Theatrical Text, Harut and Marut's play as a Model). The limits have been determined: the temporal (1965), spatial (Egypt), objective (Anthropology and Representations of Magic in Arab Theatrical Text, Harut and Marut's play as a Model), in addition to the procedural definitions of the terms mentioned in the research title. The second chapter (theoretical framework) consists of three sections, in addition to the indicators that stem from the theoretical framework. The researcher, in the first section, addressed: the emergence of magic in the ancient civilization. The researcher, in the second section, addressed the anthropology of magic. The third section is dedicated for studying magic in the world theatrical text. The third chapter is dedicated for the research procedures, wherein the research community which includes one research sample, i.e. a model for the research, has been determined, and the research sample which was limited to the play Harut and Marut by Ali Ahmad Bakathir in (1965). The researcher eventually came up with the results of the research sample analysis as follows:1- The characters of the two (angels) are considered an extension of the cultural precipitate represented by the social systems and cultural layouts prevailing in the primitive societies where magic is considered a model for them. 2- The play dealt with two forms of magic manifested by the (black magic) embodied in (jinn) and (the two angels) that were clearly visible in strange phenomena, and the (white magic) manifested in its function, where it eliminated the invisible vicious forms.The researcher, based on the results, made her conclusions, and presented a set of recommendations supported by some suggestions that she found complementary for the research. That was in the fourth chapter that the researcher dedicated for mentioning the above contents. The researcher also mentioned the list of resources.